Answers

2016-02-16T17:40:17+05:30
Let us first substitute the value of x as -2
3(-2)² -2k(-2) +2m = 0
3(4) +4k + 2m = 0
12 +4k +2m = 0
4k +2m = -12
2k+m = -6------------------------(1)

Now, Let us substitute the value of x as 3
3(3)² -2k(3) +2m  = 0
3*9 -6k +2m = 0
27 - 6k +2m = 0
-6k +2m = -27 
6k-2m = 27------------------------------(2)

(1) * 2 
⇒ 4k+2m = -12
Now consider the second equation
6k-2m = 27
4k+2m = -12
10k = 15
⇒ k = 15/10
⇒ k = 3/2 , now substitute the value of k in equation (1)
2*3/2 +m = -6
3+m = -6
⇒ m = -6-3
⇒ m = -9.
∴ The value of k = 3/2 and the value of m = -9.

Thank you.....!!!!
Mark as brainliest of helpful..
Yours, Jahnavi.
0
remember this and never again do the decimal answers ok?
becoz of this my 4 marks Has lost
thanxx for the advice
oh.......so sorry
my pleasure